2018
DOI: 10.1088/1361-6579/aae86d
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability, multifractal multiscale patterns and their assessment criteria

Abstract: Objective: Both the central nervous system and the autonomic nervous system are complex physiological networks which modulate the heart rate. They are spatially extended, have built-in delays and work on many time scales simultaneously—nonhomogeneous networks with multifractal dynamics. The object of our research was the analysis of human heart rate variability (HRV) using the nonlinear multiscale multifractal analysis (MMA) method for several cardiovascular diseases. The analysis of HRV (night-time recordings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
(58 reference statements)
0
14
0
Order By: Relevance
“…The shape depicted for the original data (part a) has a characteristic 'ridge' along the range of q parameter between 0 and 2 and for all scales s (although the 'ridge' changes direction for lower scales). Such a ridge is observed usually for healthy subjects (this 'ridge' is marked in figure 5(a) by a red ellipse) (Gierałtowski et al 2012, Kokosińska et al 2018. Figure 5(b) depicts the shape of the Hurst surface obtained from the same RR time series, but with the U-shaped patterns replaced by 1/f noise.…”
Section: Resultsmentioning
confidence: 82%
“…The shape depicted for the original data (part a) has a characteristic 'ridge' along the range of q parameter between 0 and 2 and for all scales s (although the 'ridge' changes direction for lower scales). Such a ridge is observed usually for healthy subjects (this 'ridge' is marked in figure 5(a) by a red ellipse) (Gierałtowski et al 2012, Kokosińska et al 2018. Figure 5(b) depicts the shape of the Hurst surface obtained from the same RR time series, but with the U-shaped patterns replaced by 1/f noise.…”
Section: Resultsmentioning
confidence: 82%
“…The aim of this paper is to apply the new AMMA technique to the RR intervals time series in order to see if this asymmetric technique improves the statistical performance on the MMA-based screening method (Kokosińska et al 2018) and also reveals the asymmetry inherent in heart rate.…”
Section: Introductionmentioning
confidence: 99%
“…The motivation to apply the algorithm to periods of a decrease and of an increase of the interbeat intervals using the asymmetric version of the MMA method (AMMA) is thus to enhance the possibility to interpret the results obtained during MMA analysis. In (Kokosińska et al 2018), we showed that MMA analysis allows us to distinguish various groups of patients with different diseases. On the other hand, HRA analysis has been shown to be a promising way to distinguish different pathological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Among different mechanism affected or modified by aortic-valve disease, the autonomic regulation, as assessed by heart rate variability (HRV), has been mainly examined in patients manifesting severe aortic-valve stenosis [7][8][9][10][11]. HRV refers to the interval fluctuations between consecutive heart beats [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…These fluctuations in the heart rate are modulated by many mechanisms including the interaction with the respiratory cycle (respiratory sinus arrhythmia) [14], the baroreflex mechanism [15], and the autonomic nervous system modulation of the sinus node through norepinephrine released from sympathetic nerves and acetylcholine released from the parasympathetic nerves [16]. Such studies of severe aortic-valve stenosis evaluated HRV with statistical indices (such as the standard deviation of all heart-beats intervals) and provided evidence of an overall HRV reduction that indicates an impaired heart's autonomic control, presumably involving a vagal withdrawal and an increased sympathetic activity [7][8][9][10][11]. Other HRV indices based on power spectrum analysis estimate the contribution of the sympathetic and parasympathetic modulation on the HRV fluctuations at different frequencies [12,16].…”
Section: Introductionmentioning
confidence: 99%